Pentingnya Pengetahuan Tentang Donor Darah Terhadap Kesadaran Perilaku Masyrakat - Fadilah Fadilah; Khairunisa Khairunisa; Risma Handayani; Usiono Usiono (Jurnal Anestesi, 2024)
The availability of blood is needed as an effort to cure disease and restore health. Efforts to provide blood are carried out through blood donations, namely the process of taking blood from someone voluntarily to be stored in a blood bank as blood stock and then used for blood transfusions. Blood donation services are only carried out by health workers who have the competence and ability and are only carried out in health facilities that meet the requirements. This is necessary to prevent various risks that can arise, such as disease transmission.